Create stunning HTML email that just works! - Patterson, Mathew; Safari eBooks (Collingwood, Australia : SitePoint, 2010)
"Create Stunning HTML Email That Just Works is a step-by-step guide to creating beautiful HTML emails that consistently work. It begins with an introduction to email covering topics such as: how email design differs from web design; permission based marketing, and the anatomy of an email. The book shows the reader how to plan, design, and build gorgeous HTML email designs that look great in every email program: Outlook, Gmail, Apple Mail, etc. All-important tasks like legal requirements, testing, spam compliance and known hacks and workarounds are covered"--Resource description page.
Description based on print version record.
Includes bibliographical references and index.
Keywords: HTML (Document markup language); Electronic mail messages; Electronic books